The relationship between career calling and presenteeism: the role of workaholism and self-compassion - Zhaobiao Zong; Feifei Sun; Haichao Sun; Shaoqing Su; Baojian Wei (Australian Journal of Psychology)
Objective While the relationship between career calling and its impact on organisations and employees has been well-documented, the connection between career calling and presenteeism remains unclear. This study aims to elucidate the positive relationship between career calling and presenteeism, as well as explore potential mitigation strategies. By drawing on work as calling theory and self-compassion literature, we investigate the mediating role of workaholism and the moderating effect of self-compassion in the relationship between career calling and presenteeism.Methods A time-lagged cross-sectional questionnaire was administered in three waves, with two-week intervals between each wave. A total of 218 valid responses were collected from nurses working in three hospitals located in northern China. Initially, confirmatory factor analysis was performed to establish discriminant validity. Subsequently, the SPSS macro Process 3.0 was utilised to test the mediating hypothesis, employing 5,000 bootstrap iterations to obtain 95% bias-corrected confidence intervals. Simple slope analysis was conducted to evaluate the moderating hypothesis. Finally, the estimated indirect effect and moderated mediation coefficients were calculated at both high and low values of the moderating variable to assess the moderated mediation hypothesis.Results Our research reveals the underlying mechanism of workaholism and the mitigative effects of self-compassion in the career calling and presenteeism linkage. The results indicate a positive indirect relationship between career calling and presenteeism via workaholism, and that this indirect effect is weaker when individuals exhibit higher levels of self-compassion.Conclusion The study sheds light on the relationship between career calling and workaholism and presenteeism among nurses, suggesting that self-compassion plays a pivotal role in the above relationship.